SOSIALISASI TENTANG PEMBERDAYAAN MAHASISWA TEKNIK LISTRIK BANDARA SEKOLAH KEDINASAN PERHUBUNGAN UDARA UNTUK MENJADI ASN PROFESIONAL DAN SIAP TUGAS DI SELURUH INDONESIA. - Fatonah, Feti; Desryanto, Nurhedhi; Sadiatmi, Rini; Machmiyana, Ichyu; Lamtiar, Suse; Ismail, KGS.M; Kurniawan, Wahyu (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Graduates of the aviation service vocational school, particularly those in the airport electrical engineering program, are required to possess not only strong technical competencies but also mental and social readiness to serve as Civil Servants (ASN) who may be assigned to various regions across Indonesia. This community engagement program aims to empower students through leadership training, soft skills development, and reinforcement of ASN integrity values. The methods used include interactive training sessions, field task simulations, and focused group discussions (FGDs) with alumni who have served in diverse locations. The results show an increased understanding among students regarding the challenges of placement, preparedness for cross-cultural situations, and motivation to serve as adaptive and professional civil servants. This program represents a strategic initiative to support the transition of students from academic life to the realm of public service as technical leaders in the aviation sector.